The Effectiveness of Marketing Strategies Through Social Media (Study on Ayam Koplo by Hangry Indonesia) - Kelvin Janson Ramadian; Dendy Putra Madya; Erika Dwi Agusta (Universitas Nahdlatul Ulama Sidoarjo, 2023)
With the development of technology and information, marketing can be done using social media. Ayam Koplo is a culinary business under Hangry Indonesia which also carries out marketing via social media Instagram and TikTok. This research was conducted using a qualitative approach by observing and analyzing Ayam Koplo social media. Found that marketing via social media TikTok and Instagram for the Ayam Koplo by Hangry Indonesia brand has not been effective. This is because the stage achieved in brand awareness for Ayam Koplo by Hangry Indonesia has only reached stage two, namely brand recognition. But more than that, brand awareness of Ayam Koplo by Hangry Indonesia has increased as seen from Tiktok social media followers and Instagram media impressions from January to March 2023.